Exploring corporate strategy text and cases - Johnson, Gerry (Financial Times Prentice Hall an imprint of Pearson Education, 2002)
An extensive process of market research & product development has formed the basis for this new edition. It covers all of the underlying concepts, processes of development & analytical methods of corporate strategy within a variety of organisations.